Status Gizi, Konsumsi Fast food, dan Tingkat Stres dengan Kejadian Hipertensi pada Remaja - Nurkhofifah, Sri Wahyu; Putriningtyas, Natalia Desy (Indonesian Journal of Public Health and Nutrition, 2023)
Background: Teenagers can experience hypertension because of several risk factors. Prevalence of hypertension at the age of 15-17 years nationally is 6.0% males and 4.7% females. This study aims to determine the relationship between nutritional status, fast food consumption, and stress levels with the incidence of hypertension in adolescents. Methods: This study used an analytic observation method with a cross sectional approach. The research subjects were adolescents from SMA Negeri 3 Semarang. The independent variables are nutritional status, fast food consumption, stress levels, the dependent variable is hypertension. The instruments used are DASS 42 and SQ-FFQ. Sampling using Purposive Sampling. Data analysis performed was univariate analysis, bivariate analysis with the Chi Square test. Results: statistical test results showed there was a relationship between nutritional status and the incidence of hypertension in adolescents (p=0.047). There was no relationship between fast food consumption (p=0.973), stress level (p=0.363) and the incidence of hypertension in adolescents. Conclusion: In this study there was a relationship between nutritional status and the incidence of hypertension in adolescents, but there was no relationship between fast food consumption and stress levels with the incidence of hypertension in adolescents at SMA Negeri 3 Semarang.